CHARACTERIZATION OF EXOPOLYSACCHARIDES PRODUCED BY RHIZOBIA SPECIES - Luque Castellane, Tereza Cristina [UNESP] (2015)
Increasing attention has been given, over the past decades, to the production of exopolysaccharides (EPS) from rhizobia, due to their various biotechnological applications. Overall characterization of biopolymers involves evaluation of their chemical, physical, and biological properties; this evaluation is a key factor in understanding their behavior in different environments, which enables researchers to foresee their potential applications. Our focus was to study the EPS produced by Mesorhizobium huakuii LMG14107, M. loti LMG6125, M. plurifarium LMG11892, Rhizobium giardini bv. giardini H152(T), R. mongolense LMG19141, and Sinorhizobium (= Ensifer) kostiense LMG19227 in a RDM medium with glycerol as a carbon source. These biopolymers were isolated and characterized by reversed-phase high-performance liquid chromatography (RP-HPLC), Fourier transform infrared (FTIR), and nuclear magnetic resonance (NMR) spectroscopies. Maximum exopolysaccharide production was 3.10, 2.72, and 2.50 g L-1 for the strains LMG6125, LMG19227, and LMG19141, respectively. The purified EPS revealed prominent functional reactive groups, such as hydroxyl and carboxylic, which correspond to a typical heteropolysaccharide. The EPS are composed primarily of galactose and glucose. Minor components found were rhamnose, glucuronic acid, and galacturonic acid. Indeed, from the results of techniques applied in this study, it can be noted that the EPS are species-specific heteropolysaccharide polymers composed of common sugars that are substituted by non-carbohydrate moieties. In addition, analysis of these results indicates that rhizobial EPS can be classified into five groups based on ester type, as determined